COP27 Climate Change Conference: urgent action needed for Africa and the world - Lukoye Atwoli; Gregory E. Erhabor; Aiah A. Gbakima; Abraham Haileamlak; Jean-Marie Kayembe Ntumba; James Kigera; Laurie Laybourn-Langton; Bob Mash; Joy Muhia; Fhumulani Mavis Mulaudzi; David Ofori-Adjei; Friday Okonofua; et al. (Nigerian Journal of Paediatrics, 2023)
Wealthy nations must step up support for Africa and vulnerable countries in addressing past, present and future impacts of climate change The 2022 report of the Intergovernmental Panel on Climate Change (IPCC) paints a dark picture of the future of life on earth, characterised by ecosystem collapse, species extinction, and climate hazards such as heat waves and floods1. These are all linked to physical and mental health problems, with direct and indirect consequences of increased morbidity and mortality. To avoid these catastrophic health effects across all regions of the globe, there is broad agreement—as 231 health journals argued together in 2021—that the rise in global temperature must be limited to less than 1.5oC compared with pre-industrial levels.